Perioperative Alterations in Plasma Endothelin-1 and Echocardiographic Correlates of Right Heart Function - Amar, D. (Institutional Knowledge at Singapore Management University, 2000)
Objective: To determine whether greater changes in plasma endothelin-1 (ET-1) concentrations and right ventricular systolic pressure occur after major thoracic surgery than after major abdominal operations. Design: Prospective study. Setting: University hospital. Participants: Patients undergoing elective thoracotomies (n = 12)or laparotomies (n = 10). Interventions: ET-1 was measured from blood obtained before anesthesia and again on postoperative days 1, 2, 3, and 5 (or 6). Transthoracic echocardiography was performed before surgery and on postoperative day 2 to evaluate right-sided heart function. Measurements and Main Results: After abdominal and thoracic surgery, systemic and estimated pulmonary vascular pressures were normal in both groups and unaffected by surgery. Plasma ET-1 concentrations decreased from baseline values during the first postoperative week with no differences between the groups. Conclusions: In patients without organic heart disease, plasma ET-1 levels do not increase in response to major abdominal or thoracic surgery. Whether or not plasma ET-1 concentrations are elevated in patients developing clinically significant postoperative pulmonary hypertension requires further study.